A Study to Evaluate the Effectiveness of a Structured Teaching Program on the Knowledge and Practice of Road Traffic Accident Prevention Measures Among Teenagers - Jagmeet Kaur; Harvinder Kaur (International Journal of Emergency and Trauma Nursing and Practices, 2023)
An investigation to evaluate the impact of a structured educational program on the understanding and implementation of strategies for preventing road traffic accidents among teenagers. Introduction: Accident is an accidental injury, passing or property harm happening in a grouping of occasions. Accidents don't simply occur; they are neglectfulness, indiscretion, carelessness, and flashing absence of focus. Accidents have turned into a significant reason for dismalness and mortality, particularly among the grown-ups and center. Bike crashes are found in kids underneath the age gathering of 12 years. Numerous sources indicate that adolescents are prone to injuries such as fractures, sprains, and severe wounds. During the school-age years, children cultivate a sense of accomplishment and acquire essential skills that are crucial for their functioning within society. Throughout their school years, coordination improves, and there is an increased sense of balance and rhythm, which allows for subconscious adherence to traffic rules and regulations. It is a research study aimed to evaluate the impact of a structured teaching program on the knowledge and practical application of strategies to prevent road traffic accidents among teenagers. Settings and Design: To ensure congruence with the nature of the issue and the study’s goals, a quantitative research methodology was utilized. The researchers opted for a non-probability convenient sampling technique to select a sample size of 200 undergraduate students for the current investigation. Results: The findings indicated that prior to the intervention, the average knowledge score was 16.72  1.90. However, following the implementation of the intervention, the average knowledge score significantly increased to 30.65  4.86 in the post-test assessment. The calculated paired “t” value was 49.83 which was found to be statistically highly significant at “p” < 0.000 level. In pre-test the mean score of practice was 19.12  1.90, whereas in the post-test the mean score of practice was 21.78  3.76. The calculated paired “t” value was 64.74, which was found to be statistically highly significant at “p” < 0.000 level. Conclusion: The study results demonstrated that the utilization of the Structured Teaching Program effectively improved the knowledge and practice of teenagers.
Keywords: Knowledge; Signal; cycling; practice; road safety; road-side accident; structure teaching program